FOLFIRINOX: From the ACCORD Study to 2014 - Oikonomopoulos, Georgios M; Syrigos, Konstantinos N; Skoura, Evangelia; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
In the field of treatment of pancreatic cancer, there has been significant progress lately. After the ACCORD/PRODIGE-4 study, 5-fluorouracil, leucovorin, irinotecan and oxaliplatin (FOLFIRINOX) became the standard combination for first-line chemotherapy. This led also to its use in the neoadjuvant setting in borderline resectable tumors, or locally advanced unresectable disease, improving the resectability and survival. The major disadvantage of this therapy is increased toxicity, limiting its use to young patients with no comorbidities. This arises the need to make dose reductions in clinical practice, with a possible drawback in effectiveness. The authors summarize three Abstracts (#256, #275, #305) presented at the 2014 ASCO Gastrointestinal Cancers Symposium which were focused in the use of modified forms of FOLFIRINOX, their toxicity profile and effectiveness. Reduced toxicity was observed, without affecting the effectiveness of the combination. Image: “St. Savvas” Anticancer Hospital. Athens, Greece